Characterizing and isolating protein marker in authenticating eurycoma longifolia herbal products - Aini Norhidayah, Mohamed (2016)
Eurycoma longfolia or commonly known as Tongkat Ali has been identified as a valuable product in phytochemical industry due to its reputation in enhancing sexual properties. The proliferation of E. longfolia based herbal products renders quality control measure to be an important task. Standardization should be carried out, and currently the products are standardised to eurycomanone, the primary compound in the plant. Current research is on preliminary work in developing and isolating protein as marker compound to authenticate E. longfolia herbal products. From the market, 16 Malaysian Registered Products, 14 Malaysian Unregistered Products, 12 International Products and 8 Beverages were sampled. Eurycomanone analysis revealed that 24 or 48% of the total products contained eurycomanone while 26 or 52% did not. Protein marker analysis was commenced with Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS PAGE). The results indicated that a distinctive single protein band appeared in the SDS PAGE gel of product containing E. longfolia. Further inspection by 2 dimensional gel electrophoresis (2DE) revealed that E. longjfolia consisted of four proteins, with similar molecular weight, but differed by isoelectric point. The four proteins were denoted as Marker A, B, C and D. Marker A was chosen as the ultimate marker as it was consistently presented in products containing E. longfolia. The presence and quantity of eurycomanone and Marker A in products containing E. long jfolia was comparable with minor exception for four products (C I, C4, C7, and C21). Marker A was isolated using subsequent size exclusion chromatography and anion exchange chromatography. The purity of Marker A was proven by the appearance of single spot in 2DE gel, with the same electrophoretic profile of Marker A in E. longfolia extracts. Marker A then characterized by MALDI TOF MS and partially sequenced using de novo sequencing method. Marker A consisted of 22 amino acids. This study has led to the isolation of homogenous protein that can be utilized as novel and comparable marker to the chemical marker; eurycomanone, to authenticate E. longfolia products. Being a protein, subsequently an antibody can be developed and incorporated into biosensor device.